História oral de vida de mulheres que vivenciaram violência doméstica - Soares, Maria Cidney da Silva (2017)
Violence against women is part of everyday life in cities, countries and worldwide. It is a daily, growing, serious public health problem which is important because it is also a crime; Therefore, deserves the public sectors´ attention regarding women's health. Some individuals remain in the domestic violence cycle for many years or for life; however, some seek ways to overcome and break the cycle. Thus, this study aims to: Know the life history of women who experience domestic violence; To investigate how the domestic violence process has developed in their lives; Identify the strategies used by these women in facing domestic violence and disclose if there were any sequels left after the domestic violence cycle was broke. To produce the empirical material, the oral life history technique - indicated by the Reference Center for Women's Care in the city of Campina Grande/PB - was used with five women. The analysis and interpretation of the material was based on the meaning units (themes) which were more evident and constant in the narratives and in the vital tone of each story. Thus, the following thematic axes were elaborated: Thematic axis I: Life trajectory of countryside women who experience domestic violence; Sub-theme I - The blossoming of flowers among the spines; Thematic axis II - Breaking the domestic violence cycle: Facing and overcoming movements; Thematic Axis III - Injured Flowers: Marks left by domestic violence. The study followed the ethical observances proposed by Resolution 466/12 and was approved by the Research Ethics Committee under CAAE: 50968615.5.0000.5188. In the narrated stories, it was observed that the women referred to their mothers´ history repetition in their lives, relating the violence situation experienced by their mothers and reproduced in their relationships. They report to had experienced the first moment of violence in their adolescence and that the physical aggression began or intensified during the gestational period and silence was present for a long time in their relationships until the complaint. They report having experienced physical, psychological, patrimonial, institutional and sexual violence. These women were able to initiate an empowerment process as they discovered their inner potential and were able to self-defend, conquer, advance and overcome not only the adversities but also the obstacles that kept them trapped in the cycle of violence. It was also present in their narratives, after the cycle break, the fear of new relationships and loneliness. Therefore, the support of professionals from all sectors involved in facing domestic violence is encouraged, promoting women autonomy and empowerment in violent situations to support them in the process of resilience.